No tabula rasa – political literacy by preschoolers (Pedagogical Horizons, 2021)
On the basis of research reports and empirical findings, the article argues that political education should already be given the space in day-care centers that corresponds to the UN Convention on the Rights of the Child. Because even pre-school children can perceive politics and integrate it into their world views. They are not politically unrelated beings, they ask questions and have knowledge about politics. Those who ignore their political literacy make it difficult to connect to political learning in primary education and contribute to alienating the concepts of democracy and politics. Participation experiences are not enough to protect against populists. Only genuine early childhood political education can safeguard democracy.
Keywords: Political Education; Early Childhood Education